Increased Electrical Conductivity of PANi: Anionic Surfactant Addition during Emulsion Polymerization. Issue 1 (22nd June 2020) - Hafizah, Mas A. E.; Mahar, Ahmad L.; Suparno; Andreas; Manaf, Azwar
Abstract: Electrically conductive polyaniline (PANi) doped with anionic surfactants is successfully synthesized and characterized. The conductive PANi is prepared by chemical oxidation polymerization reaction with the addition of two types of anionic surfactant solutions respectively 1% Sodium Octyl Sulfate (NaC8 H17 SO4, SOS) and Sodium Dodecyl Sulfate (NaC12 H25 SO4, SDS), followed by doping with a strong perchloric acid (HClO4 ). The addition of each surfactant solution has increased the electrical conductivity value of surfactant free PANi from 0.089 to 1.16 S cm −1 (SOS) and 1.12 S cm −1 (SDS) respectively. The viscosity value of surfactant free PANi is 1.97 mPa s which is much lower when compared with those of PANi containing surfactants in which the value is 3.58 and 4.20 mPa s for 1% of SDS added PANi each. The chain length of anionic surfactant has no major effect on the conductivity of PANi. The latter is only affected by the presence of SO3 − group in hydrophobic part of surfactant.